Pengembangan Perangkat Pembelajaran Kimia SMA Berbasis Masalah untuk Meningkatkan Pemahaman Konsep dan Kemampuan Berpikir Kritis Peserta Didik - Lembang, Fransisca Rante; Danial, Muhammad; Salempa, Pince (Program Pasca Sarjana UNM, 2019)
The study is Research and Development (R&D), which aims at designing Chemistry learning device SMA (senior high school) based on problem to improve conceptual understanding and critical thinking skills of students on Thermochemistry material and discovering whether the quality of Chemistry learning device product has met validity, practicality, and effectiveness. The development model used in this study referred to 4-D development model by Thiagarajan which covered 4 stages, namely (1) define, (2) design, (3) development, and (4) dissemination. The device developed in this study: Lesson Plan (RPP), Student’s Workbook (LKPD), and Learning Test (THB). The result of the study reveal that each stage of the result of development referred to the procedure of learning device development model based on problem. The device developed has met the product quality, namely 1) device validity with the mean score 3.68 in very valid category, 2) the practically which covered: a) learning device implementation with the mean score 1.77 in ‘entirely implemented’, b) learning management of teacher with the mean score 3.68 in good category, c) teacher’s response on the device was 3.75 in practical category and with no revision, and 3) the effectiveness covered: a) the student’s learning activity was 91.1% which met very good criteria, b) the student’s response was 80% which met very responsive criteria, c) conceptual understanding test with the mean score of pretest 18.6% in very low category, the mean score of posttest 87.5% in high category, and the result of N-gain 0.8 in high category, d) critical thinking skills with the mean score of pretest 18.3% in very low category, the posttest was 77.9% in high category, and the result of N-gain 0.73 in high category.